T52. COGNITION, METACOGNITION AND SOCIAL COGNITION AFTER A FIRST EPISODE PSYCHOSIS. PRELIMINARY RESULTS FROM A 5-YEAR-FOLLOW-UP STUDY. (18th May 2020) - Tripoli, Giada; Quattrone, Diego; Huang, Xiaoyang; Rose, Danielle; Rodriguez, Victoria; Ferraro, Laura; Del Peschio, Simona; Gayer-Anderson, Charlotte; La Cascia, Caterina; La Barbera, Daniele; Morgan, Craig; Sham, Pak; et al.
Abstract: Background: Cognitive impairment is considered a core feature of psychotic disorders. Deficits in cognition, metacognition and social cognition have been reported to be correlated, and indeed predictors, of functional outcome or level of disability. Psychotic patients tend to present lower IQ and show impairment in specific cognitive domains, and in social cognition, than controls. Several studies have found deficits in facial emotion recognition (FER) and a higher prevalence of the jumping to conclusions (JTC) reasoning and data gathering biases among psychotic patients, even at time of illness onset, compared to controls. However, the trajectory of this impairment remains unclear. Only a few studies have jointly investigated longitudinally the course of neurocognitive and social cognitive deficits, emotional processing, and JTC. Therefore, this study aimed to explore long-term trajectories of IQ, JTC, and FER using 5-year follow up (FU) data. Methods: 36 patients with First Episode Psychosis (FEP) and 70 controls from the London subsample of the EUGEI study were followed up after 5 years. Sociodemographic, clinical and neuropsychological assessments were performed at baseline and 5-year-follow-up. Current IQ was measured using WAIS III short form, JTC bias through the 60:40 beads task, and FER using Degraded Facial Affect Recognition (DFAR) task. In STATA 15, repeated measures ANOVA was used to analyse changes between baseline and follow up scores. Results: Mean IQ scores for patients were 88.4 (20) at baseline and 92.6 (SD 17.9) at FU. For controls, IQ scores were 104.5 (SD 18.4) at baseline and 108.9 (SD 19.5) at FU. For patients, mean number of beads was 3.9 (SD 4) at baseline and 3.2 (SD 3.4) at FU, while controls decided after 6.3 (SD 4.6) beads on average at baseline and 6.5 (SD 3.2) at FU. For patients, mean DFAR scores were overall [baseline: 72.5 (SD 16); FU: 72.4 (SD 18.1)], neutral [baseline: 79 (SD 19.1); FU: 76.5 (SD 24.3)], happy [baseline: 86.9 (SD 16.9); FU: 88.4 (SD 18.9)], fearful [baseline: 51.3 (25.6); FU: 54.2 (SD 20.9)], angry [baseline: 72.8 (24.3); FU: 70.4 (26.9)]. For controls, mean DFAR scores were overall [baseline: 76.3 (SD 8.6); FU: 75.4 (SD 8.7)], neutral [baseline: 82.2 (SD 12.8); FU: 84.9 (SD 13.1)], happy [baseline: 93 (SD 7.9); FU: 90.7 (SD 8.5)], fearful [baseline: 60.5 (18.1); FU: 58.1 (SD 20.3)], angry [baseline: 69.5 (19.5); FU: 58.1 (20.3)]. Repeated-measures ANOVA showed that patients scored significantly lower than controls on: IQ [F(1, 103) = 22.6, p < 0.001], beads task [F(1, 104) = 12.5, p = 0.0006], DFAR overall [F(1, 101) = 6.94, p = 0.0096], DFAR neutral [F(1, 101) = 10.36, p = 0.0017], DFAR happy [F(1, 101) = 7.88, p = 0.0059] and DFAR fearful [F(1, 101) = 5.45, p = 0.0213]. There was a significant effect of time for IQ scores [F(1, 103) = 19.4, p > 0.001], but no time*group interaction. There was no significant main effect of time or time*group interaction for beads task and all DFAR scores. Discussion: In line with previous literature, lower IQ was found in the patients group, both at baseline and 5-year-follow-up. Likewise, jumping to conclusion bias and facial emotion recognition impairments were prominent in patients compared to controls. Preliminary Results: pointed out small yet significant improvement in current IQ for both groups. Nonetheless, JTC bias and deficits in recognising emotional facial expressions were found to be steady along the course of the illness. Further research is warranted to examine the association between those impairments and functional outcome.